ACM International Conference on Interactive Media Experiences 2021
DOI: 10.1145/3452918.3458796
|View full text |Cite
|
Sign up to set email alerts
|

Moderation Visibility: Mapping the Strategies of Volunteer Moderators in Live Streaming Micro Communities

Abstract: Volunteer moderators actively engage in online content management, such as removing toxic content and sanctioning anti-normative behaviors in user-governed communities. The synchronicity and ephemerality of live-streaming communities pose unique moderation challenges. Based on interviews with 21 volunteer moderators on Twitch, we mapped out 13 moderation strategies and presented them in relation to the bad act, enabling us to categorize from proactive and reactive perspectives and identify communicative and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…A group of research involving volunteer mods often treats them as individual entities to conduct the moderation practices, such as the moderation tools they have used [7,35] and the different roles they have played in the community [55,59,70]. These roles involve various tasks and moderation strategies, such as helping the streamer to manage viewers [71] and communicating with violators [9].…”
Section: Related Work 31 Volunteer Moderation and Remote Collaborationmentioning
confidence: 99%
See 3 more Smart Citations
“…A group of research involving volunteer mods often treats them as individual entities to conduct the moderation practices, such as the moderation tools they have used [7,35] and the different roles they have played in the community [55,59,70]. These roles involve various tasks and moderation strategies, such as helping the streamer to manage viewers [71] and communicating with violators [9].…”
Section: Related Work 31 Volunteer Moderation and Remote Collaborationmentioning
confidence: 99%
“…The application of moderation strategies and doing tasks requires much communication and coordination. Though some work points out the discussion among other mods or the admin (e.g., [9,61]), there is a lack of work to investigate mods collaboration and coordination mechanism. This work extends existent research in volunteer moderation regarding mods' individual decision-making to the collective decision-making process for two reasons.…”
Section: Related Work 31 Volunteer Moderation and Remote Collaborationmentioning
confidence: 99%
See 2 more Smart Citations
“…Kiene et al [47] also found that the moderation tools are insufficient for organizing and retrieving information for mods to make consistent decisions towards violations and that mods seek user-developed bots to track information of community members. Research in live streaming communities shows that some mods use moderation tools to check a viewer's history [7] but are not satisfied with the features of these tools and hope to have more information about viewers and violators [5]. While this thread of research discusses the need and necessity of more evidence for moderation, they do not specify what type of evidence they need, how they collect the evidence, and consequently, how to use these shreds of evidence to evaluate potential violations and punish potential violators.…”
Section: Applying Criminal Profiling To Community Moderation and In Live Streamingmentioning
confidence: 99%